2018
DOI: 10.1016/j.otsr.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Is distal femoral torsion the same in both of a patient's legs? Morphometric CT study

Abstract: IV (retrospective cohort study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Intraobserver reliabilities were also assessed with intraclass correlation coefficients (ICCs) and 95% confidence intervals (CIs). Previous studies have already shown good interobserver agreement [7, 30].…”
Section: Methodsmentioning
confidence: 85%
“…Intraobserver reliabilities were also assessed with intraclass correlation coefficients (ICCs) and 95% confidence intervals (CIs). Previous studies have already shown good interobserver agreement [7, 30].…”
Section: Methodsmentioning
confidence: 85%